2006
DOI: 10.1080/09658210444000476
|View full text |Cite
|
Sign up to set email alerts
|

Remembering a criminal conversation: Beyond eyewitness testimony

Abstract: Unlike the important body of work on eyewitness memory, little research has been done on the accuracy and completeness of "earwitness" memory for conversations. The present research examined the effects of mode of presentation (audiovisual/ auditory-only) on witnesses' free recall for utterances in a criminal conversation at different retention intervals (immediate/delayed) within a single experiment. Different forms of correct recall (verbatim/gist) of the verbal information as well as different types of erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
4
38
1
Order By: Relevance
“…In other of our studies using a free-recall test, parallel findings concerning superior correct recall in the audiovisual modality compared to the auditory-only modality over time have been observed (Campos & Alonso-Quecuty, 2006). However, contrary to our findings when using a recognition memory test, participants had very poor verbatim recall for sentences (less than 1% correct).…”
Section: Memory For Conversation and The Legal Contextcontrasting
confidence: 55%
See 3 more Smart Citations
“…In other of our studies using a free-recall test, parallel findings concerning superior correct recall in the audiovisual modality compared to the auditory-only modality over time have been observed (Campos & Alonso-Quecuty, 2006). However, contrary to our findings when using a recognition memory test, participants had very poor verbatim recall for sentences (less than 1% correct).…”
Section: Memory For Conversation and The Legal Contextcontrasting
confidence: 55%
“…The videotape was used in previous research (Campos, 2005;Campos & Alonso-Quecuty, 2006). In the film, both talkers were standing up during the conversation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Memories lacking perceptual quality are more prone to misinformation (Belli, 1989). Nevertheless, other studies have also found that auditory memory is relatively more distortable than visual memory (Campos & Andalonso-Quecuty, 2006). …”
Section: Unfamiliar Voice Identificationmentioning
confidence: 94%